A global risk assessment of primates under climate and land use/cover scenarios. (27th May 2019) - Carvalho, Joana S.; Graham, Bruce; Rebelo, Hugo; Bocksberger, Gaëlle; Meyer, Christoph F. J.; Wich, Serge; Kühl, Hjalmar S.
Abstract: Primates are facing an impending extinction crisis, driven by extensive habitat loss, land use change and hunting. Climate change is an additional threat, which alone or in combination with other drivers, may severely impact those taxa unable to track suitable environmental conditions. Here, we investigate the extent of climate and land use/cover (LUC) change‐related risks for primates. We employed an analytical approach to objectively select a subset of climate scenarios, for which we then calculated changes in climatic and LUC conditions for 2050 across primate ranges ( N = 426 species) under a best‐case scenario and a worst‐case scenario. Generalized linear models were used to examine whether these changes varied according to region, conservation status, range extent and dominant habitat. Finally, we reclassified primate ranges based on different magnitudes of maximum temperature change, and quantified the proportion of ranges overall and of primate hotspots in particular that are likely to be exposed to extreme temperature increases. We found that, under the worst‐case scenario, 74% of Neotropical forest‐dwelling primates are likely to be exposed to maximum temperature increases up to 7°C. In contrast, 38% of Malagasy savanna primates will experience less pronounced warming of up to 3.5°C. About one quarter of Asian and African primates will face up to 50% crop expansion within their range. Primary land (undisturbed habitat) is expected to disappear across species' ranges, whereas secondary land (disturbed habitat) will increase by up to 98%. With 86% of primate ranges likely to be exposed to maximum temperature increases >3°C, primate hotspots in the Neotropics are expected to be particularly vulnerable. Our study highlights the fundamental exposure risk of a large percentage of primate ranges to predicted climate and LUC changes. Importantly, our findings underscore the urgency with which climate change mitigation measures need to be implemented to avert primate extinctions on an unprecedented scale. Abstract : For all 426 primate species available in the IUCN database, we assessed species' exposure risk to projected changes in climatic and land use/cover conditions for the year 2050 under a best‐ and a worst‐case scenario. Our analyses revealed that Malagasy primates will be the least affected by climate change, whereas effects will be most pervasive in the Neotropics, likely exposing especially forest‐dwelling primates to highly elevated temperatures across their ranges. Across most species' ranges, undisturbed habitat is expected to be replaced by disturbed habitat, and pervasive crop expansion is forecast particularly across the ranges of Asian and African primates.